Evaluation And Production Of Dolime And Magnesia From Rimba Mas Dolomite Perlis - Ariffin, Hamdan (2014)
Dolomite deposit of Rimba Mas, Perlis is one of the major, high quality and significant resource in Malaysia with total inferred reserve of 630 million metric tonne, and normally exploited for low-end as grits for agriculture and construction industries. In this research, evaluation for potential of value-added product development of the resource for high-end and advanced product applications in higher economic sector were envisaged and explored especially for calcined and high quality compound of Magnesia (MgO) production. Geologically, petrographically and chemically indicated that Rimba Mas indeed a high grade dolomite rock (>99.0%) and often with marginal impurities (,0.6%). The lime (CaO), Magnesia and LOI (C02) contents are generally 32.78%,20.01% and 46.6% respectively. Generally, dolime (MgO.CaO) of the resource is absolutely acceptable and possessed a good calcination value, attained at optimum temperature of about 1000°C@90 minutes soaking time, a low decrepitating «1.00%) and settling rate. Qualitative and quantitative XRD analyses (using rietveld method) performed on the similar batch of dolime also show the similar trends, where the total amount of MgO and Mg(OH)2 components are significantly high about 46.50% with the lowest CaC03 «6.50%) fraction. Whilst, re-carbonation test have successfully generated high pure MgO compound. Initial test also proved the possibility of Magnesia extraction through the modified Pattinson's process route is feasible with the yield over 99.00%, however additional test works and economic evaluation are necessary.